Efeito citotóxico e pró-apoptótico do composto [6]-Shogaol contra células de câncer de bexiga (MB49), in vitro - Nina, Diana Gabriela Nina (Universidade Federal de São Carlos, 2021)
Bladder cancer is considered one of the most aggressive malignancies due to its profile of recurrence and progression, and even with the improvement in methods of diagnosis and treatment, the mortality rate has not shown a declining trend in recent decades worldwide. In this perspective, the search and development of more effective and safer therapeutic alternatives is necessary. Phytochemicals are excellent sources of active ingredients with therapeutic potential, which have been used for centuries for therapeutic and culinary purposes. [6]-Shogaol is a phenolic compound extracted from the rhizome of ginger (Zingiber officinale Roscoe) that has shown antiproliferative and anti-tumor effects in a wide variety of cancer models, both in vitro and in vivo. However, there are no records of studies reporting an antitumor effect in cell models of bladder cancer. Thus, this study aimed to investigate the in vitro cytotoxic and pro-apoptotic potential of [6]-Shogaol against murine bladder cancer urothelial cells (MB49), in relation to non-tumor murine fibroblasts (L929). Through the in vitro study, the cytotoxic and pro-apoptotic effect was evaluated, through the analysis of the reduction of the metabolic activity, observation of morphological alterations associated with cellular damage, identification of alterations in the process of colony formation, evaluation of the level of reactive species of intracellular oxygen, evaluation of alterations in the nuclear structure, identification of apoptosis events and assessment of anti-migratory potential. Based on the results, it was shown that [6]-Shogaol was able to induce cytotoxic effects that compromised cell viability, exhibiting an inhibitory concentration of 50% of cells (IC50) of 135,5 µM for tumor cells MB49 and 205,3 µM for L929 non tumor fibroblasts, in addition to inhibiting and altering the proliferative processes of colony formation, showed pro-apoptotic activity identified by the observation of apoptotic phenotypes, mediated by nuclear fragmentation. In summary, our study suggests that [6]-Shogaol causes cytotoxic damage that compromises the viability of MB49 murine bladder tumor cells in a concentration-dependent manner. It can be suggested that [6]-Shogaol is promising for delineation in more in-depth studies to understand its antitumor properties, as it is a strong phytotherapeutic candidate in the treatment of bladder cancer.
cytotoxic and pro-apoptotic effect of [6]-Shogaol compound against bladder cancer cells (MB49), in vitro
Keywords: Câncer de bexiga; Citotóxico; Fitoterápico; Pró-apoptótico [6]-Shogaol; Bladder cancer; Cytotoxic; Phytotherapic; Pro-apoptotic [6]-Shogaol; IC50; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA